Source of stressors and emotional disturbances among undergraduate science students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi; Ali, Syed Masroor; Mohamed Ismail, MaungKoHajee (Sumathi Publications, 2014)
Introduction: Higher education is considered as a stressful period in students’ life which they have to cope with since they are facing a variety of demands such as living away from their families, a heavily loaded curriculum, and inefficiency in both mentor- mentee and health education programs. This will make them more vulnerable to emotional disturbances such as stress, anxiety and depression. Methodology: A total of 194 undergraduate students from Kulliyyah (Faculty) of Science, International Islamic University Malaysia participated in questionnaire-based study using the Depression Anxiety, Stress Scale (DASS-21) to assess the severity of emotional disturbances Results: The overall prevalence of depression, anxiety and stress was 64.4%, 84.5% and 56.7% respectively. Regarding the severity of the symptoms, it was found that 13.9%, 51.5 % and 12.9% of the students have clinically significant depression, anxiety and stress respectively. Young students aged 21 years and below had a statistically significant association with depression, anxiety and stress. While first year students had significant association with depression. Regarding the source of stressors, the top ten stressors decided by the students were mainly academic and personal factors. Conclusion: Emotional disturbances in the form of depression, anxiety and stress are existing in high rate among undergraduate science students that require early intervention. Factors including feeling of incompetence, lack of motivation to learn and difficulty of class work can be considered as source of stressors that may precipitate for depression anxiety and stress.